Botswana and Zimbabwe: Relative success and comparative failure - Guy Mhone; Patrick Bond (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2001)
Botswana and Zimbabwe represent two cases of differential access to the world economy. Notwithstanding its lack of diversification and its reliance on a primary mineral export, Botswana has prospered while Zimbabwe has fallen into a deep crisis. Historical and comparative evidence allows us to transcend the superficial presumption common to much policy discourse, namely, that the basis for success depends upon adherence to the `Washington Consensus' export-oriented strategy, or to good governance, or even to geographical considerations. We argue instead that there are much deeper problems and possibilities that Botswana and Zimbabwe unveil, which relate largely to developmental linkages and aspects of agency.
Keywords: F13; F43; O19; O49; O54; O55; 330; sub-Saharan Africa; critique of the Washington consensus; Wirtschaftslage; Exportdiversifizierung; Botsuana; Simbabwe